MANIPULATIVE TACTICS IMPLEMENTATION IN POLITICAL DISCOURSE - Tatyana P. Paliy; Inna N. Poteryakhina (Sovremennye Issledovaniâ Socialʹnyh Problem, 2024)
Background. The political discourse of modern society is a complex, multi-faceted and multi-level entity characterized by a variety of goals and objectives and functioning within the framework of current political, economic, geopolitical, cultural and other realities. Linguistic analysis of modern political discourse and, in particular, identification of the most frequent linguistic means of implementing manipulation in political discourse, is of particular relevance today and is important not just because it expands the theoretical scientific base, but for its practical value for the formation of a mature point of view and critical thinking when dealing with the texts of political discourse.